Investigating the integration of drone management systems to create an enabling remote piloted aircraft regulatory environment in South Africa - Nkamisa, Siyanda (My University, 2021)
The emerging technology of remote piloted aircraft is touted as an innovative device with potential to transform various industries. It is important for South Africa to create an enabling regulatory environment for commercial remote piloted aircraft to succeed and contribute positively to the economy of the country. However, commercial remote piloted aircraft are heavily regulated in South Africa with inefficient compliance processes and poor enforcement mechanisms. The study interrogates the South African remote piloted aircraft regulatory environment, juxtaposing it with global regulatory trends to better understand existing gaps and opportunities that can be capitalised. To address gaps, this study investigated drone management systems as tools that can be used to facilitate a friendly remote piloted aircraft regulatory environment. The deterrence model is extended in this study to form a theoretical and conceptual framework to regulate remote piloted aircraft. The researcher used an interpretivism case study methodology, collecting qualitative data from published documents such as policies, legislation, regulations and professionals working in the remote piloted aircraft regulatory environment. The findings of this study support the belief that the South African remote piloted aircraft regulatory environment is cumbersome and unfriendly. Even though South Africa has an effective remote piloted aircraft regulatory environment, it is negatively impacted by efficiency challenges. The South African remote piloted aircraft regulations replicated the manned aircraft regulations resulting in remote piloted aircrafts being over-regulated and stifled as a technology. Furthermore, the South African remote piloted aircraft regulatory environment has weak enforcement mechanisms which opens room for fraudulent activities. The study recommends the integration of drone management systems in the South African remote piloted aircraft regulatory environment. At a fundamental level, drone management systems can be used to facilitate a friendly licensing and enforcement environment. One vital feature that needs to be developed for drone management systems to be highly effective for all stakeholders is the inclusion of flight information management. The availability of this feature could potentially lead to the relaxation of the requirements to attain a licence for beyond visual line of sight operations and services.
A dissertation submitted to the Faculty of Humanities, University of the Witwatersrand in partial fulfilment of the requirements for the degree of Masters of Arts (in the field of ICT Policy and Regulation), (MA ICTPR), 2021